PENERAPAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DI RUMAH SAKIT IBU DAN ANAK (RSIA) SITTI KHADIJAH GORONTALO - Putri ramadani Hudju (Jurnal Sistem Informasi dan Bisnis Cerdas, 2026)
Research was conducted at Sitti Khadijah Hospital Gorontalo, with the aim of implementing a personnel management information system. Currently, personnel data management is still done manually, resulting in challenges in data retrieval, employee information updates, and personnel report preparation. Furthermore, another important issue is the lack of a notification or reminder system regarding the validity period of the Practice Permit (SIP) for clinical healthcare workers. This system was developed using the Prototype development method, which has seven stages: requirements gathering, prototype development, prototype evaluation, system coding, system testing, system evaluation, and system use. The development of this system uses the Laravel framework as the primary framework and MySQL as the database to store all information. The result of this research is a web-based system or software the Personnel Management Information System at the Sitti Khadijah Women’s and Children’s Hospital (RSIA) in Gorontalo.